Intraductal Papillary Neoplasm of the Bile Ducts: Case Reports with Review of the Literature - Dayananda Lingegowda; Anisha Gehani; Sumit Mukhopadhyay; Divya Midha; Sudeep Banerjee; Bharat Gupta (Thieme Medical and Scientific Publishers Pvt. Ltd., 2021)
Intraductal papillary neoplasm of the bile duct (IPNB) is a rare variant of bile duct tumors, which is a counterpart of pancreatic intraductal papillary mucinous neoplasm (IPMN). These tumors need to be differentiated from other common bile duct tumors such as cholangiocarcinoma, as IPNB carries a better prognosis. A combination of enhancing intraluminal papillary filling defect, demonstrating washout and associated upstream and downstream biliary dilation, should raise the suspicion of IPNB.